Membrane bioreactor for wastewater treatment: A review - Al-Asheh, Sameer (2021)
Due to the growth in the human population globally, it is noted that various industries have also grown. The need for an excess supply of water and the generation of high effluent quality upon proper treatment technologies has become a necessity. These two crucial needs can be achieved with the aid of membrane bioreactor (MBR) that has been proven to be effective in removing organic and inorganic matters as a biological unit for wastewater treatment. MBR plants are created by integrating the biological process with membrane filtration which possesses numerous benefits if compared with conventional methods such as activated sludge; MBR is widely used for municipal and industrial wastewater treatment. This review addresses basic concepts of MBRs plants and subsequently provides information on the recent developments of each part related to MBR plants. The characteristics of the bioreactor treatment process is discussed in detail, and then a comprehensive review of the membrane separation process is examined. The fouling phenomena as a main obstacle to widespread MBRs plant is presented in detail with recent fouling mitigation methods. The efforts of a number of novel MBR processes are summarized. In order to tackle the existing limitation of MBRs to be practical on a larger scale, the existing challenges and future research efforts are proposed.